2009
DOI: 10.1590/s1516-14392009000400023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of polypropylene/calcium carbonate nanocomposites

Abstract: The aim of this work was to study the influence of calcium carbonate nanoparticles in both tensile and impact mechanical properties of a polypropylene homopolymer. Four compositions of PP/CaCO 3 nanocomposites were prepared in a co-rotational twin screw extruder machine with calcium carbonate content of 3, 5, 7 and 10 wt. (%) The tests included SEM analyzes together with EDS analyzer and FTIR spectroscopy for calcium carbonate, tensile and impact tests for PP and the nanocomposites. The results showed an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 22 publications
2
78
0
4
Order By: Relevance
“…In previous work we showed that calcium carbonate nanoparticles leads to great increase in elastic modulus and reduction in brittle-to-ductile transition temperature, which means that the filler has a toughening effect in polypropylene. The results obtained in this work were correlated with the reinforcement effect of calcium carbonate in the case of elastic modulus and with the stress concentration factor of calcium carbonate in polypropylene in the case of toughening effect 7 . Among all the effects that calcium carbonate nanoparticles can achieve in the crystallization of PP, some have been extensively reported in literature; formation of PP β phase as a consequence of the nucleation effect of the nanoparticles, higher crystallization temperature, lower half crystallization time and higher degree of crystallinity 5,6 .…”
Section: Introductionmentioning
confidence: 55%
“…In previous work we showed that calcium carbonate nanoparticles leads to great increase in elastic modulus and reduction in brittle-to-ductile transition temperature, which means that the filler has a toughening effect in polypropylene. The results obtained in this work were correlated with the reinforcement effect of calcium carbonate in the case of elastic modulus and with the stress concentration factor of calcium carbonate in polypropylene in the case of toughening effect 7 . Among all the effects that calcium carbonate nanoparticles can achieve in the crystallization of PP, some have been extensively reported in literature; formation of PP β phase as a consequence of the nucleation effect of the nanoparticles, higher crystallization temperature, lower half crystallization time and higher degree of crystallinity 5,6 .…”
Section: Introductionmentioning
confidence: 55%
“…When the nanoparticle content increased, they tended to form agglomerates that could be described as particles with higher dimensions (the obtained aqueous colloidal suspension having 2 wt % of TiO 2 content). Dispersions were subsequently stirred vigorously for 45 min [28][29][30].…”
Section: Preparation Of Tio 2 Nanocoatingmentioning
confidence: 99%
“…One such example is the use of CaCO 3 particles to toughen the shell layer, and it was found that the CaCO 3 reinforced thermoplastics had higher mechanical strengths than pure thermoplastic [7]. This toughening was also observed when nanosize CaCO 3 particles were added, leading to enhancements in the mechanical properties of WPCs, such as improved modulus of elasticity (MOE), modulus of rupture (MOR), and impact strength [8][9][10]. In addition, talc, inorganic plate-shaped filler, has been used as an additive in WPCs to improve their thermal and mechanical properties [11,12].…”
Section: International Journal Of Polymer Sciencementioning
confidence: 99%